Bibliometric Analysis of Numeracy and Mathematical Problem-Solving Skills in Mathematics Education (2020–2026) - Zulfa Wildatussaumi; Nila Munana; Santi Alfifat Khurosyidah; Muji Suwarno (Gema Cendekia Institute, 2026)
Numeracy skills and mathematical problem-solving are two key competencies in mathematics education in Indonesia that continue to develop significantly. However, no bibliometric study has specifically mapped the research development on both topics in an integrated manner. This study aims to map publication trends, author collaboration networks, and thematic clusters of research on students' numeracy and mathematical problem-solving skills in mathematics learning during the period 2020–2026. The method used is bibliometric analysis with data sourced from Google Scholar via the Harzing's Publish or Perish application. From 994 initial documents, 77 articles were selected based on thematic relevance, mathematics subject focus, and Indonesian language. Data were analyzed using Microsoft Excel and visualized using VOSviewer. The results show an increasing publication trend with a peak in 2025. The most productive authors are Fauziyah, Nur and Wintarti, Atik with the highest Total Link Strength (TLS) score of 4. MATHEdunesa is the most productive journal, while Jurnal Ilmiah Matematika Realistik has the highest citation impact (355 citations). Keyword cluster analysis yielded 6 main clusters covering national context (AKM), numeracy characteristics, problem-solving strategies, assessment, error analysis, and learning processes. Topics still rarely explored include error analysis, gender perspectives, and the application of Polya's theory. These findings are expected to serve as an intellectual map for researchers and educators in determining future research directions on numeracy and mathematical problem-solving.